Acanthosis Nigricans: An overt clinical marker of insulin resistance and its association with serum adiponectin levels in obese pediatric population - Rupinder Walia; Amandeep Riyat; Baljinder Kaur; Maninder Kaur; Shayna Aulakh; Dimple Chopra (Indian Journal of Paediatric Dermatology, 2022)
Background: Childhood obesity (OB) is becoming increasingly prevalent in recent times. Acanthosis nigricans (AN) is a clinical condition linked to OB and insulin resistance (IR). Serum adiponectin is one of the major adipokines that is inversely related to the severity of IR. Objective: The main aim of this study is to evaluate the correlation of severity (grades) of AN with serum adiponectin levels and IR. Materials and Methods: A total of 80 subjects were studied, 50 having OB with AN (OB+AN) and 30 having OB without AN (OB-AN), having age 10–18 years fulfilling the set inclusion and exclusion criteria. Body mass index, fasting blood glucose, HOMA-IR (Homeostatic Model Assessment of IR) and serum adiponectin levels were measured in all subjects. Results: Compared to OB-AN group, OB+AN group had statistically significant lower serum adiponectin levels and higher HOMA-IR values. AN grades correlated positively with HOMA-IR values and negatively with serum adiponectin levels in a statistically significant manner. Conclusion: Grading AN clinically can be easy and useful tool to detect IR in obese subjects. Serum adiponectin levels can be used as another lab parameter in obese subjects guiding the severity of AN.